2014
DOI: 10.1099/vir.0.057695-0
|View full text |Cite
|
Sign up to set email alerts
|

A conserved C-terminal sequence of high-risk cutaneous beta-human papillomavirus E6 proteins alters localization and signalling of β1-integrin to promote cell migration

Abstract: Beta-human papillomaviruses (b-HPV) infect cutaneous epithelia, and accumulating evidence suggests that the virus may act as a co-factor with UV-induced DNA damage in the development and progression of non-melanoma skin cancer, although the molecular mechanisms involved are poorly understood. The E6 protein of cutaneous b-HPV types encodes functions consistent with a role in tumorigenesis, and E6 expression can result in papilloma formation in transgenic animals. The E6 proteins of high-risk a-HPV types, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…A specific characteristic of the oncogenic mucosal HPV types is a PDZ-binding motif on the carboxyl terminus of E6, which is important in cell proliferation, cell polarity and cell transformation (Cavatorta et al, 2004). Although the PDZbinding domains were not found at the carboxyl terminus of the novel γ-PV types here described, it has been shown that the E6 proteins of some oncogenic β-PV types encode a conserved domain (YXDM) at the carboxyl terminus which alters the localization and signalling of the β1-integrin that was associated with increased cell migration, and therefore with a higher pathogenicity of these β-HPV types (Holloway and Storey, 2014). Binding partners and possible functions of the different conserved C-terminal motifs of the E6 proteins should be explored in order to investigate the pathological mechanism of some γ-PV types.…”
Section: Discussionmentioning
confidence: 84%
“…A specific characteristic of the oncogenic mucosal HPV types is a PDZ-binding motif on the carboxyl terminus of E6, which is important in cell proliferation, cell polarity and cell transformation (Cavatorta et al, 2004). Although the PDZbinding domains were not found at the carboxyl terminus of the novel γ-PV types here described, it has been shown that the E6 proteins of some oncogenic β-PV types encode a conserved domain (YXDM) at the carboxyl terminus which alters the localization and signalling of the β1-integrin that was associated with increased cell migration, and therefore with a higher pathogenicity of these β-HPV types (Holloway and Storey, 2014). Binding partners and possible functions of the different conserved C-terminal motifs of the E6 proteins should be explored in order to investigate the pathological mechanism of some γ-PV types.…”
Section: Discussionmentioning
confidence: 84%
“…Hpv-positive NPC tends to have a poor prognosis [ 42 ]. It has been shown that the conserved C-terminal sequence of the E6 protein of high-risk cutaneous β-HPV promotes cell migration by altering β1-integrin localization and signaling, which may be involved in contributing to the pathogenicity of these β-HPV types [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructural studies show integrin chains’ distribution in the basal cell layer of the squamous epithelium, which is crucial for the interaction between the epithelium and basal lamina [ 20 ]. The interactions between them can be altered during the first steps of dysplastic transformations that come before micro-invasive cervical cancer [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%